The performances of Romanian agriculture, given the resources allotted in the socialist agricultural system, compared to the market economy - Liliana Miron; Aurel Lup (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The agricultural performances depend, on the one hand, on the volume, structure and quality of the resources allotted, and, on the other hand, on their management, according to the economic system and to the national policies in the field. This article draws a parallel between the two agricultural systems, i.e. the socialist-planned type and the private one, typical of the market economy. The following periods are compared: 1986-1989 for the former type and 2006-2009 for the latter type of agriculture. The comparison targets the main resources: the agricultural real estate (surface, structure and quality), land reclamations and fertilizers. Between 1986 and 1989, the agriculture benefited from generous resources: over three million ha equipped for irrigations, modern orchards and vineyards, large amounts of fertilizers; as a whole, a more intensive technological system in terms of inputs. The yields increased, especially in cereals. Two decades later, i.e. between 2006 and 2009, the agriculture became extensive. Irrigation decreased by 10 times, a large part of the vineyards and orchards were destroyed, the amount of fertilizers was reduced to 1/3 compared to the 1986-1989 period. In terms of performance, the Romanian agriculture became extensive during the market economy, but there are relatively few differences in the results expressed by the yield level. These express the difference in the technological level between the two periods, due to several causes that we are going to analyze in the article.
Keywords: 330; performances; land reclamation; planed economy; market economy